2020
DOI: 10.3389/fmed.2020.00410
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Cut-Off Value of the Fecal Immunochemical Test for Symptomatic Patients Does Not Improve Diagnostic Performance

Abstract: Introduction: The fecal immunochemical test (FIT) has been established as a cost-effective test in colon cancer screening programmes. This test could also be helpful in symptomatic patients prior to colonoscopy, but data about diagnostic performance, and accurate cut-off values for these patients are still scarce. Materials and Methods: Prospective study that included consecutive unselected patients with gastrointestinal symptoms referred for colonoscopy between November 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
2
10
0
1
Order By: Relevance
“…When compared to FC, the specificity for MH in UC was similar, but FIT appeared to be more sensitive than FC for predicting MH (95% vs 77% for MES = 0 in a study by Hiraoka et al [ 17 ], 98.0% vs 78.4% for MES = 0, 94.9%, vs 74.6% for UCEIS 0-1 in a study by Ryu et al [ 18 ]). One of the main advantages of using FIT over FC refers to cutoff values of FIT, which are relatively stable and almost equivalent to the cutoff values used in colorectal cancer screening[ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…When compared to FC, the specificity for MH in UC was similar, but FIT appeared to be more sensitive than FC for predicting MH (95% vs 77% for MES = 0 in a study by Hiraoka et al [ 17 ], 98.0% vs 78.4% for MES = 0, 94.9%, vs 74.6% for UCEIS 0-1 in a study by Ryu et al [ 18 ]). One of the main advantages of using FIT over FC refers to cutoff values of FIT, which are relatively stable and almost equivalent to the cutoff values used in colorectal cancer screening[ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the cost of FIT is cheaper than that of FCP [106]. In addition, the cut-off value of FIT is relatively stable compared to FCP, which is almost the same as the cut-off value used in screening for colorectal cancer [107].…”
Section: Fitmentioning
confidence: 87%
“…Overall, the search had identified 121 articles for FIT and 133 articles for VOC. Among them, 15 studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were included for FIT meta-analysis and 14 studies [10][11][12][13][35][36][37][38][39][40][41][42][43][44] for VOC meta-analysis. The selection process of the studies, for both meta-analyses, are shown in the PRISMA diagram-Figure 1.…”
Section: Re Sultsmentioning
confidence: 99%